Role of Ca2+/Calmodulin-Dependent Protein Kinase Type II in Mediating Function and Dysfunction at Glutamatergic Synapses - Mohanan, Archana G.; Gunasekaran, Sowmya; Jacob, Reena Sarah; Omkumar, R. V. (Frontiers in Molecular Neuroscience, 2022)
Glutamatergic synapses harbor abundant amounts of the multifunctional Ca2+/calmodulin dependent protein kinase type II (CaMKII). Both in the postsynaptic density as well as in the cytosolic compartment of postsynaptic terminals, CaMKII plays major roles. In addition to its Ca2+-stimulated kinase activity, it can also bind to a variety of membrane proteins at the synapse and thus exert spatially restricted activity. The abundance of CaMKII in glutamatergic synapse is akin to scaffolding proteins although its prominent function still appears to be that of a kinase. The multimeric structure of CaMKII also confers several functional capabilities on the enzyme. The versatility of the enzyme has prompted hypotheses proposing several roles for the enzyme such as calcium signal transduction, memory molecule function and scaffolding. The article will review the multiple roles played by CaMKII in glutamatergic synapses and how they are affected in disease conditions.